Perceptions of performativity in English Further Education. Issue 1 (2nd January 2022) - Poole, Richard
ABSTRACT: The notions of performativity and the use of accountability practices within the UK education sector are contentious. Although some commentators suggest that statistically driven performativity measures do not align with practitioner values, little research has investigated any potential differences in relation to job role and level of management responsibility. This study focused on whether perceptions of performativity change according to someone's job role and whether there is a differential between managers and teachers. An electronic questionnaire was disseminated at a single FE college, with 107 participants surveyed across a wide range of subject areas. Quantitative analysis revealed that perceptions of managers differ from those of teaching staff regarding the effectiveness of statistical performativity targets to drive factors which are integral to an efficacious learning environment. Results are far from unequivocal though. As practitioners take on more of a managerial emphasis within their role, the perceived benefit of and their affinity for target setting and performativity measures increase. However, the magnitude of this more favourable outlook towards performativity is limited, with managers also broadly sceptical concerning any benefit and positive impact that target setting practices can have.